Effect of temperature on the water diffusion in claystone: Tournemire case - Marc Fleury; Maiwenn Humbezi Desfeux; Manuel Marcoux; Jean-Michel Matray (Applied Clay Science, 2026)

Thermal properties of low Arctic vegetation and peat: Coupled experimental quantification and numerical modelling for Western Siberian Lowlands - Simon Cazaurang; Manuel Marcoux; Michel Quintard; Sergey V. Loyko; Artem G. Lim; Oleg S. Pokrovsky; Laurent Orgogozo (Cold Regions Science and Technology, 2026)

Solute Transport in Bentonite Buffer Under Thermal Hydraulic Mechanical Coupling - Uy D. Vo; Mamadou Fall; Julio Á. I. Sedano; Maïwenn Humbezi-Desfeux; Jean-Michel Matray; Manuel Marcoux; Son T. Nguyen (Geotechnical and Geological Engineering, 2026)
This paper investigates solute transport processes in the bentonite buffer of a Deep Geological Repository (DGR) for used nuclear fuel, using the Canadian concept as an example. The design relies on a multi-barrier system in which the used fuel container (UFC) provides containment and the surrounding bentonite buffer protects the UFC while retarding radionuclide migration following a potential breach. Solute transport in the buffer is strongly influenced by coupled thermal-hydraulic-mechanical (THM) processes. A coupled THM-transport model was developed to evaluate (1) reactive transport of bisulfide $$\left({\text{H}\text{S}}^{-}\right)$$ HS - from the host rock to the UFC and associated UFC corrosion; and (2) radionuclide migration following a hypothetical UFC breach. The model builds on previous verification and validation and is further assessed against laboratory-scale bisulfide transport experiments and a large-scale thermal diffusion experiment at the Tournemire Underground Research Laboratory (France). The results show that temperature-dependent diffusion is the dominant transport mechanism, significantly enhancing solute migration, whereas hydraulic desaturation has limited influence and the Soret effect is negligible at repository scale. Under the reference conditions, adsorption and $$\text{F}\text{e}\text{S}$$ FeS precipitation delay detectable HS − flux to the UFC until approximately 5 × 10 5 years and limit the predicted corrosion depth to ~ 0.05 mm after one million years. In the breach scenario, the buffer effectively delays and attenuates moderately/strongly sorbing radionuclides (e.g., 135 Cs, 237 Np). The effectiveness in retarding radionuclides' migration is most sensitive to bentonite diffusivity and sorption capacity.

Numerical simulation of solute transport in argillaceous rock under thermal gradient with a coupled THM-solute transport model - Uy Vo; Mamadou Fall; Julio Ángel Infante Sedano; Maïwenn Humbezi-Desfeux; Jean-Michel Matray; Manuel Marcoux; Thanh Son Nguyen (Geomechanics for Energy and the Environment, 2025)

Fast Upscaling of the Hydraulic Conductivity of Three-Dimensional Fractured Porous Rock for Reservoir Modeling - Tawfik Rajeh; Rachid Ababou; Manuel Marcoux; Israel Cañamon (Mathematical Geosciences, 2019)

Determination of Chlorinated Solvent Sorption by Porous Material—Application to Trichloroethene Vapor on Cement Mortar - Marion Musielak; Mark L. Brusseau; Manuel Marcoux; Candice Morrison; Michel Quintard (Transport in Porous Media, 2014)